HIV-1 Infection Impairs Regulatory T-Cell Suppressive Capacity on a Per-Cell Basis - Angin, Mathieu (Oxford University Press, 2014)
The impact of CD4(+) regulatory T cells (Tregs) on human immunodeficiency virus type 1 (HIV-1) pathogenesis remains incompletely understood. Although it has been shown that Tregs can be infected with HIV-1, the consequences of infection on a per-cell basis are still unknown. In vitro HIV-GFP infected and noninfected Tregs were isolated by flow-based cell-sorting to investigate Treg suppressive capacity and gene expression profiles. Our data show that HIV-1-infected Tregs were significantly less suppressive than noninfected Tregs and demonstrated down-regulation of genes critical to Treg function. This impaired function may have detrimental consequences for the control of generalized immune activation and accelerate HIV disease progression.